2020
DOI: 10.12688/wellcomeopenres.16106.2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intimate partner violence and abuse among adolescents and young adults: findings from a UK population-based cohort

Abstract: Background: Approximately one-third of young people in the UK have suffered intimate partner violence and abuse (IPVA) on reaching adulthood. We need interventions to prevent IPVA in this population, but there is a lack of evidence on who is at greatest risk. Methods: We analysed questionnaire data from 3,279 participants of the Avon Longitudinal Study of Parents and Children population-based birth cohort. We estimated the prevalence of IPVA victimisation and perpetration by age 21, by sex, demographic, parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 40 publications
(6 reference statements)
2
26
0
Order By: Relevance
“…We analysed data on 3279 young people who were part of the ALSPAC (Avon Longitudinal Study of Parents and Children, formerly ‘Children of the 90s’) birth cohort study, and who had answered questions relating to IPVA (delivered in online and paper form) at 21 years old. Demographic, behavioural, and health characteristics of this sample are described in Herbert et al, Extended Data, Table C ( Herbert et al, 2021 ). Briefly, two-thirds were female, with a median age of 21 years (interquartile range: 21–22); women and men were more likely to be of low socioeconomic deprivation levels than high (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We analysed data on 3279 young people who were part of the ALSPAC (Avon Longitudinal Study of Parents and Children, formerly ‘Children of the 90s’) birth cohort study, and who had answered questions relating to IPVA (delivered in online and paper form) at 21 years old. Demographic, behavioural, and health characteristics of this sample are described in Herbert et al, Extended Data, Table C ( Herbert et al, 2021 ). Briefly, two-thirds were female, with a median age of 21 years (interquartile range: 21–22); women and men were more likely to be of low socioeconomic deprivation levels than high (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Among young people in the UK, it is estimated that one-third to three-quarters are exposed to Interpersonal Violence and Abuse (IPVA) victimization by 21 years old, and one fifth perpetrate IPVA ( Barter, 2009 ; Herbert et al, 2021 ; Young et al, 2018 , 2019 ). Evidence mainly from north America suggests poor mental and physical outcomes in young people who experience IPVA ( Goncy et al, 2017 ; Haynie et al, 2013 ; Sessarego et al, 2021 ), and so effective interventions for its prevention and related outcomes are needed ( Barter & Stanley, 2016 ; Campbell et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The available evidence on the impact of sexual violence in mid-adolescence on mental health is scarce, as much attention pre-adulthood has been given to adverse childhood experiences, including sexual abuse earlier in childhood, 9,10 experiences of sexual violence in the university and college environment, 11,12 and intimate partner violence in older adolescent age groups. 13 Several existing studies we identified that focused on mid-adolescence, an age at which many begin to experience increasing levels of sexual harassment and assault after puberty, are limited in their ability to make assumptions on the population level impacts of sexual violence due to either the use of selective samples, such as those recruited from sexual assault referral centres, 14 the examination of crosssectional associations, 15,16 or the use of retrospective recollections of both violence experienced and its perceived subsequent impact on mental health. 8,17 As for the studies with any longitudinal examination, these were limited to convenience samples in some North American school settings, 18,19 and do not include relevant wider and earlier life factors that might be important confounders of this relationship.…”
Section: Introductionmentioning
confidence: 99%